2019
DOI: 10.1175/jhm-d-19-0032.1
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Variations in Precipitation Amount, Frequency, Intensity, and Persistence in China, 1973–2016

Abstract: In this paper, we examined the spatial and temporal variations in precipitation amount, frequency, and intensity in China based on daily precipitation data from 2050 weather stations from 1973 to 2016. We used two Markov chain parameters to quantify the wet persistence and dry persistence that characterizes the temporal pattern of wet and dry days, respectively. We found that China’s annual precipitation changed little from 1973 to 2016, but varied dramatically from 524 to 688 mm yr−1, with an average of 592 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 66 publications
2
11
0
Order By: Relevance
“…From Figure 3(B), it can be found that, the amount of rain day (precipitation >1 mm) has significantly changed in 38% China's area, mainly increased in the Qinghai-Tibet Plateau (west China) and decreased in northwest China. This suggests that the precipitation increase in western China is due to the increase in both precipitation frequency and intensity, which is consistent with the results of Shang et al (2019). Figures 3(C) and 3(d) show the trends of RX1day and RX5day, where 18% and 16% of grid points in China have a statistically significant change trend.…”
Section: Trend Of Extreme Precipitation Indicessupporting
confidence: 85%
“…From Figure 3(B), it can be found that, the amount of rain day (precipitation >1 mm) has significantly changed in 38% China's area, mainly increased in the Qinghai-Tibet Plateau (west China) and decreased in northwest China. This suggests that the precipitation increase in western China is due to the increase in both precipitation frequency and intensity, which is consistent with the results of Shang et al (2019). Figures 3(C) and 3(d) show the trends of RX1day and RX5day, where 18% and 16% of grid points in China have a statistically significant change trend.…”
Section: Trend Of Extreme Precipitation Indicessupporting
confidence: 85%
“…In particular, numerous studies on summer precipitation changes in China have detected interdecadal variations since the late 1970s (Wang et al, 2017, Ma et al, 2021. The annual precipitation has increased significantly in southeast, northeast, and western China and decreased from southwest China to northeast Inner Mongolia during the past decades (Shang et al, 2019). Autumn precipitation and rainy days in WC exhibited a significant reduction before the 1990s and increased after the 2000s (Yuan and Liu 2013;Wang et al, 2015;, but the precipitation intensity has been enhanced (Wang et al, 2015;Zhang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Although no significant change has been observed in the long-term trend of annual precipitation in China, the interdecadal, interannual, and regional variations are remarkable (Zhai et al 2005;Shang et al 2019). Regionally, extreme heavy rainfall has shown a significant trend of increase and light rainfall has shown a significant trend of decrease over central eastern China.…”
Section: Introductionmentioning
confidence: 99%